Philosophical-Psychological, Pedagogical-Managerial Aspects of "Qualitative" Formation of Future Specialists of All Levels of Training and Specialties in the Conditions of Technical University - Ihnatiuk, O. A.; Kostyria, I. V.; Koss, A. M. (Shiny World Corporation, Canada, 2022)
The study is devoted to such topical issues in the theory and methodology of education and pedagogy of higher education as the training of future leaders, namely the formation and development of leadership qualities of students in technical universities. On the topic of the study, the authors analyzed the literature of leading scientists in the field of philosophy, psychology and pedagogy, identified features of the formation of leadership in the student environment. The study reveals the seven most important criteria that form the core of the personality of the future specialist leader. The use of these seven criteria of personality development of the future specialist in technical universities requires a combination and adaptation of traditional approaches to education and the latest pedagogical technologies. This is aimed not just at introducing certain forms and methods of work into the educational process, but at creating a specially organized professional environment in which future professionals have opportunities for professional and personal growth through conscious change and transformation of both the environment and themselves. In the process of personal change, the student's historical "I" is as close as possible to his logical "I" and is held by the latter with the help of Onto In-Se. This is how the future specialist acquires leadership qualities, first of all: cognitive, communicative, organizational, moral and volitional and reflexive skills. It is established that through the development of conceptual and creative thinking of the student it is possible to influence the formation of his critical "I" as a necessary attribute of leadership: the ability to listen and hear, understand and act.
Keywords: formation; future specialist; Technical University; leadership skills; "I" is a student; In Se Ontico